2017
DOI: 10.1097/mlr.0000000000000689
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Nurse Practitioners, Physician Assistants, and Primary Care Physicians’ Patterns of Practice and Quality of Care in Health Centers

Abstract: Across the outcomes studied, results suggest that NP and PA care were largely comparable to PCMD care in HCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(120 citation statements)
references
References 34 publications
5
111
0
4
Order By: Relevance
“…At the population level, nursing practice laws may improve the healthcare ecosystem available for the entire spectrum of injury sequelae, from health promotion and risk reduction of violence against self or others to emergency injury treatment and follow-up care that prevents injury mortality. Prior studies of nursing practice laws have found an effect on healthcare resources and patient outcomes as they relate to inpatient hospitalization and medical care [27,28]. Our study extends these findings by linking nursing practice laws to injury outcomes and suggesting that nurses are beneficial to population health outcomes more broadly than has been identified previously.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…At the population level, nursing practice laws may improve the healthcare ecosystem available for the entire spectrum of injury sequelae, from health promotion and risk reduction of violence against self or others to emergency injury treatment and follow-up care that prevents injury mortality. Prior studies of nursing practice laws have found an effect on healthcare resources and patient outcomes as they relate to inpatient hospitalization and medical care [27,28]. Our study extends these findings by linking nursing practice laws to injury outcomes and suggesting that nurses are beneficial to population health outcomes more broadly than has been identified previously.…”
Section: Discussionsupporting
confidence: 78%
“…Scope-of-practice laws for NPs are a contentious policy issue in the US, with some states allowing independent practice for NPs without physician oversight and others requiring physician oversight for all APRN practice [26]. There is substantial evidence that increasing NP scope of practice is not only safe and effective, but also increases access to care for underserved populations [27][28][29]. For RNs, the key law affecting their practice is the Nurse Licensure Compact.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies reported lower quality of HIV care by general medicine non‐HIV experts. Several other studies have reported delivery of non‐HIV–specific primary care by NPs and PAs that is at least comparable in quality to care provided by physicians . Our study was the first to examine physicians, nurse practitioners, and physician assistants providing HIV care at different types of facilities in both high‐ and low‐prevalence areas, representative of the diversity of U.S. HIV care providers.…”
Section: Discussionmentioning
confidence: 92%
“…Although PAs and NPs differ in their professional philosophies and training, the scope of services they deliver in healthcare settings is often equivalent. 15,34 To obtain robust estimates, PAs and NPs were combined into a singular provider type, consistent with research where the sample size is not large enough to report on each type of provider. 22,35 …”
Section: Methodsmentioning
confidence: 99%